2021
DOI: 10.3390/idr13040088
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Rise in Seroprevalence of SARS-CoV-2 Infections in Children in Western Germany—A Blind Spot in Epidemiology?

Abstract: SARS-CoV-2 infection rates in children and adolescents are often underestimated due to asymptomatic or oligosymptomatic infections. Seroprevalence studies can reveal the magnitude of “silent” infections in this age group and help to assess the risk of infection for children but also their role in spreading the disease. In total, 2045 children and their parents from the Ruhr region were finally included after the exclusion of drop-outs. Seroconversion rates among children of all age groups increased from 0.5% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…A population-based study in Geneva also observed lower seroprevalence rates among younger (6–9 years old) children [ 23 ]. Moreover, in this study, high rates of seroconversion were observed in multiple pediatric age groups, a finding also reported in German and Danish studies [ 4 , 24 ]. However, a large cohort study in Canada observed that younger children were more likely than older children to transmit SARS-CoV-2 infection to other household members, suggestive of divergent dynamics of disease transmission [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A population-based study in Geneva also observed lower seroprevalence rates among younger (6–9 years old) children [ 23 ]. Moreover, in this study, high rates of seroconversion were observed in multiple pediatric age groups, a finding also reported in German and Danish studies [ 4 , 24 ]. However, a large cohort study in Canada observed that younger children were more likely than older children to transmit SARS-CoV-2 infection to other household members, suggestive of divergent dynamics of disease transmission [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…People below 18 years of age comprise nearly 34% of the Indian population [ 1 ], but prior to the emergence of newer variants of concern accounted for <5% of the total burden of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections [ 2 ]. Global evidence is indicative of children and adolescents having less susceptibility to SARS-CoV-2 infection than adults, with much lower rates of severe coronavirus disease 2019 (COVID-19) [ 3 , 4 ]. A retrospective analysis of mortality data from the state of Odisha in India with a population of approximately 43 million reported only 36 COVID-19-related child deaths through August 2021 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a standardised approach from 1 June 2020 to 1 February 2021, all asymptomatic children and adolescents from 6 months to 18 years of age who attended outpatient paediatric practices in three regions of Germany for scheduled mandatory routine examinations were invited to participate in the study (Corkid study, 'Corona in Kids') [ 3 ]. Participants and their parents were asked to fill in an electronic questionnaire (pre-installed on a tablet) with 14 questions (see Supplementary material ) available in five different languages (German, English, Turkish, Arabic and Russian).…”
Section: Methodsmentioning
confidence: 99%
“…Children are frequently oligo- or asymptomatic and therefore undertested and underdiagnosed. Seropositivity studies, however, reveal that the rate of SARS-CoV-2 infections in adults and children is similar [ 1 - 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may become problematic if a variant emerges that causes more severe disease in these age groups than previous variants. Yet, we cannot rule out the possibility that we underestimated the extent of under-ascertainment in these age groups, as the factors we used where informed by seroprevalence studies based on blood samples donated by adults (ages 18-74), while it has been reported that under-ascertainment ratios can assume values ranging from 2 up to 6 or 8 for children [29][30][31].…”
Section: Resultsmentioning
confidence: 99%